1994
DOI: 10.1128/jcm.32.7.1663-1668.1994
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of PCR and other diagnostic techniques for detection of Helicobacter pylori infection in dyspeptic patients

Abstract: A sensitive and specific PCR-based assay to detect the Helicobacter pylon 16S rRNA gene present in formalin-fixed paraffin-embedded gastric biopsy specimens has been developed. A total of 95 patients with dyspepsia were evaluated for the presence of chronic active gastritis and an infection with H. pylori through the use of diagnostic assays based on biopsy specimens and serology. The "gold standard" for the presence of the bacteria was direct detection in histological sections of biopsy specimens by Giemsa st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
21
0
1

Year Published

1995
1995
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 70 publications
(24 citation statements)
references
References 34 publications
(39 reference statements)
2
21
0
1
Order By: Relevance
“…The rapid-urease test and histological examinations of biopsy specimens detected H. pylori infection in slightly fewer patients than did culture but they still yielded good specificity, although they gave some false-positive results (two and one, respectively). Overall, our results are in good agreement with other recent data for comparisons of different routine tests for H. pylori in which Giemsa staining of histological sections (26) or the agreement among all the tests was taken as the gold standard (13). In both studies PCR assays detected H. pylori infection in a higher percentage of patients.…”
Section: Discussionsupporting
confidence: 91%
“…The rapid-urease test and histological examinations of biopsy specimens detected H. pylori infection in slightly fewer patients than did culture but they still yielded good specificity, although they gave some false-positive results (two and one, respectively). Overall, our results are in good agreement with other recent data for comparisons of different routine tests for H. pylori in which Giemsa staining of histological sections (26) or the agreement among all the tests was taken as the gold standard (13). In both studies PCR assays detected H. pylori infection in a higher percentage of patients.…”
Section: Discussionsupporting
confidence: 91%
“…Initial evidence of H. pylori presence in environmental water samples has come from PCR amplification of samples obtained from Colombia, where infection rates are over 90% (Handwerker et al 1995). In addition to this a number of PCR assays have been utilized over the years for the detection of H. pylori in water (Engstrand et al 1992;Weiss et al 1994;Hulten et al 1996;Sasaki et al 1999;Benson et al 2004;Gomes & De Martinis 2004;Shahamat et al 2004). In this study real time qPCR was shown to be a specific, sensitive and rapid method to quantify H. pylori in sewage.…”
Section: Transmission Of H Pylori In Watermentioning
confidence: 84%
“…We demonstrated that the icd primers were more specific for H. pylori than the species-specific protein antigen primers when tested against a variety of DNA samples. Others have used primers based on the 16S rRNA, which have also displayed good specificity when tested against many microorganisms, including several Helicobacter species (16,25), although no studies have been performed to assess the detection limit of these primers for H. pylori in feces.…”
Section: Discussionmentioning
confidence: 99%